Mulheres num cenário interétnico: concepções do HIV e aids em repertórios interculturais - Lima, Édija Anália Rodrigues de (2021)
Introduction: Aids confrontation experiences have showed that the vulnerable social areas are the backbone of HIV dissemination, in particular, the ones of interethnic nature, focusing the women who reside in. Objective: To analyze from the perspective of the interculturality the meanings attributed to HIV and aids that compound the repertories of indigenous and no indigenous women. Method: Descriptive, retrospective study that used as theoretical basis the Interculturality. CCAE: 32503714.4.0000.5188 The data originate from the Word Association Test applied to 386 no indigenous women and 256 indigenous women, between the ages of 18 and 65, who came from the region of Rio Tinto-PB and used the inducing word aids. The corpus was imported and processed in IRaMuTeQ® Textual Analysis software, being carried out the Descending Hierarquical Classification, Factorial Correspondence analysis and additional analyses. Results: In both groups prevailed from 30 to 45 and marital status married/stable relationship. There was an association between the ethnical groups and the variables: belief (p-valor 0,030), conjugality (p-valor 0,028), schooling (p-valor 0,001) and income (p-valor <0,001). Three classes were formed: Biomedical repertoire – made reference to the biomedical knowledge; Socioemotional repertoire - referred to negative elements of social and emotional characteristics; and Behavioral repertoire - reflected a set of behaviors and practices related to HIV and aids infection. The biomedical was the most significant to both groups, being led by no indigenous women; indigenous women mostly represented socioemotional and behavioral constituents. The supplementary specifities analysis allowed the comparison of the ethnical groups from the frequency of the words in question. The Factorial Correspondence analysis showed the words positioning that led to convergence and divergence interpretation, received in the study. Final Consideration: In this interethnic scenario the intercultural dialogue materializes in the heterogeneous forms exchange of thinking-knowing-doing, that unfolds, under the relational and functional interculturality influence, presenting embryonic movements to the critical interculturality.